The Consecration of the Τemple of the Holy Sepulcher in the Context of the Council of Tire (335) - Damyanoiva, Ekaterina (Forum Theologicum Sardicense, 2025)
Ekaterina Damyanova, The Consecration of the Temple of the Holy Sepulchre in the Context of the Council of Tire (335). At the beginning of the 4th century, Emperor Constantine I the Great (306–337) built a new empire on the foundations of Christianity. With the support of imperial funds and the Palestinian bishops under the leadership of Eusebius of Caesarea (260–340), large basilicas were erected in Bethlehem, Jerusalem, and Hebron. The festive events of the consecration of the Basilica of the Holy Sepulchre in Jerusalem were overshadowed by quarrels among the clergy and a trial in absentia. A council was convened by the emperor in the city of Tyre, but St. Athanasius (296/8–373) was not physically present at the proceedings against him.